Master gardener [videorecording (DVD)] - Schrader, Paul, 1946-; Edgerton, Joel, 1974-; Weaver, Sigourney, 1949-; Swindell, Quintessa, 1997-; Morales, Esai; Losan, Eduardo; Hill, Victoria, 1971-; Le, Amy; Dynan, Alexander, 1985-; Rodriguez, Benjamin, Jr; Hynes, Devonté, 1985- (Magnolia Home Entertainment, 2023)
Master Gardener follows Narvel Roth, the meticulous horticulturist of Gracewood Gardens. He is as much devoted to tending the grounds of this beautiful and historic estate, to pandering to his employer, the wealthy dowager Mrs. Haverhill. When Mrs. Haverhill demands that he take on her wayward and troubled great-niece Maya as a new apprentice, chaos enters Narvel's spartan existence, unlocking dark secrets from a buried violent past that threaten them all.